Profil Keterampilan Berpikir Kritis Siswa SMA Negeri 4 Tasikmalaya Pada Pembelajaran Biologi - Ramdani, Dani; Latifah, Hilma Nuri; Triyanto, Samuel Agus (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Critical thinking skills are one of the essential competencies that need to be developed in the learning process, especially in biology subjects that require in-depth analysis of natural phenomena. This study aims to analyze the profile of students' critical thinking skills at SMA Negeri 4 Tasikmalaya in biology learning. The research method used is quantitative descriptive. The sample used was 181 grade X students. The critical thinking ability data in this study was measured through 12 written essay test questions. The data analysis technique used in this study was the reliability and validity of the instrument to ensure that the critical thinking skills measurement instrument used was reliable and valid. This research is very important to do as one way to analyze the profile of critical thinking skills in biology learning. The results of the study of students' critical thinking skills on the Interpretation indicator showed a percentage of 36.61% with a low category, the Analysis indicator showed a percentage of 68.08% with a high category, the Evaluation indicator showed a percentage of 58.82% with a medium category, the Inference indicator showed a percentage of 45.92% with a medium category, the Explanation indicator showed a percentage of 39.76% with a low category, and the Self-regulation indicator showed a percentage of 73.02% with a high category. Based on these data, it can be seen that the average critical thinking skills of students is 53% which can be classified as moderate critical thinking skills. The results of the study can provide a significant contribution in improving the quality of biology education at SMA Negeri 4 Tasikmalaya, by encouraging the development of students' critical thinking skills that will be useful for them in academic environments and everyday life.